The changed landscape - Robinson, M. J.; Schneider, J. (Olympic & Paralympic Coach, 2015)
De Bosscher, Bingham, Shibli, van Bottenburg, and DeKnop (2008) cited that there are widely accepted factors which contribute to elite sport success and that these factors can be classified on three levels: the social and cultural context in which people live (macro-level), the athlete and their close environment (micro-level), and sport policies and politics (meso-level). Past research has attributed a good part of the elite sport success for a country to macro-level variables such as gross domestic product (GDP), population, geography, and climate. U.S. sport has clearly benefited from these macro variables with one of the world largest populations and Gross Domestic Products (GDP) and multiple climates. The U.S. has also benefited from micro-variables such as the strength of the sport culture in the United States as well as the American cultural characteristics of competiveness, individualism, willingness to take risk and challenging authority (Hofstede, Hofstede & Minkov, 2010). De Bosscher et al. (2008) identified nine meso-level variables associated with international sport success that include: financial support, integrated approach to policy development, foundation and participation in sport, talent identification and development system, athletic and post career support, training facilities, coaching provision and development, international competition and scientific research. Recently, the macro-type variables from which the U.S. has benefited have been neutralized to some degree by smaller countries being more strategic in addressing the meso-level variables. Along with this, the micro-variable of strength of sport culture, which may be positive, can become counterproductive to growth and development. These realities have enabled competitor countries to close the competitive gap and in some instances pass the U.S. Albert Einstein once stated that "everything has changed, but the way we think." Thus, the U.S. must change the way we think to find the remedy to the symptom mentioned above. What is being said is neither new to the leaders of the United States Olympic Committee (USOC) nor the National Governing Bodies (NGBs). The challenge for them is communicating the message to those most responsible for the recruitment, development and training of athletes: the leaders and coaches coaching in the youth sport environment. While all of the nine variables are important, the responsibility for participation and talent identification and development falls to these professionals and organizations.